Multimodality Analysis in YouTube Educational Content: Case Study on the Realization of Meaning in SUARA BERKELAS Video “Kalau Kamu Mau Punya CRITICAL THINKING, Jangan Skip Obrolan Ini!” - Nisa Silitonga; Selly Sitompul; Sonya Pasaribu; Sonya Silitonga; Muhammad Natsir (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
In the digital era, YouTube has become a powerful platform for sharing knowledge, shaping perspectives, and encouraging critical engagement. This study explores how multimodal elements—verbal, visual, and audio—construct meaning in the educational video “Kalau Kamu Mau Punya Critical Thinking, Jangan Skip Obrolan Ini!” from the Suara Berkelas channel. Using a qualitative case study approach, the research interprets how these modes work together to support critical thinking. Data were collected through video observation, transcription, and documentation of multimodal features, then analyzed thematically using Kress and van Leeuwen’s multimodal framework and Facione’s critical thinking model. The findings show that the verbal mode structures logical arguments and rhetorical appeals, the visual mode emphasizes meaning through gestures, expressions, and text overlays, while the audio mode builds emotional engagement through tone, pauses, and background music. Together, these modes create a coherent and persuasive discourse that not only informs but also invites viewers to reflect critically. The study contributes theoretically to the understanding of multimodality in digital education and practically provides insights for educators and content creators to design more interactive, reflective, and engaging educational content.